On the growth and structure of Al2O3-Y3Al5O12-ZrO2:Y solidified eutectic. Issue 8 (July 2020) - Cherif, M.; Duffar, T.; Carroz, L.; Lhuissier, P.; Bautista-Quisbert, E.
Abstract: Structural features of Al2 O3 -YAG-ZrO2 :Y eutectic plates grown by the EFG process have been studied. X-ray tomography shows that all three phases are continuous along the whole sample, suggesting a fully coupled ternary eutectic growth. However the growth of alumina and YAG is well described by a classical binary coupled growth, in spite of the facetted structure of their growth interface. Colonies are observed at high growth rate and have been related to the chemical rejection of zirconium ions at the solid-liquid interface, possibly due to a slight off-stoechiometry of the raw material.